Effect of fibre loading on the microstructural, electrical, and mechanical properties of carbon fibre incorporated smart cement-based composites - Zhang, Jiacheng; Heath, Andrew; Ball, Richard J.; Paine, Kevin (Frontiers in Materials, 2022)
Carbon fibre incorporated smart cement-based composite has great potential for the multifunctional health monitoring of concrete structures. This paper presents the microstructural, electrical, and mechanical properties of smart cement-based composites incorporating chopped carbon fibres from low dosages at 0–0.1% by volume (vol%) with detailed intervals, to high dosages up to 2.4 vol%. In comparison to a plain mortar, smart cement-based composites at all fibre contents had higher flexural strength. A 95% improvement in flexural strength was obtained at a fibre content of 0.3 vol%, whereas compressive strength increased up to a fibre content of 1.0 vol%, with the highest improvement, 105%, at 0.2 vol%. The bulk conductivity of smart cement-based composites underwent a double percolation process where the percolation zone of the fibres was identified at fibre contents of 0–0.1 vol% and the percolation zone of the capillary pores resided at fibre contents of 2.1–2.4 vol% indicating an extremely low durability. This study presents the laboratory characterization on smart cement-based composites where the fundamentals of the transitional behaviours of the mechanical properties and the percolation in electrical property through fibre loading were studied, which is a necessary step prior to the assessment of the self-sensing performance. The impact of this study will enable the physical properties of carbon fibre incorporated smart cement-based composites to be optimized through the design and manufacturing process. This will lead to robust performance and superior in-situ multi-functional health monitoring of concrete structures.